Exploring the Synergic Effects of Nursing Home Work on Work-Related Musculoskeletal Disorders Among Nursing Assistants. (March 2018) - Ching, Shirley S. Y.; Szeto, Grace; Lai, Godfrey Kin Bun; Lai, Xiao Bin; Chan, Ying Tung; Cheung, Kin
Little is known about how nursing assistants (NAs) perceive the nature of their work and how their work contributes to work-related musculoskeletal disorders (WMSDs). This qualitative study addressed these gaps. Twenty-four NAs with WMSDs working in four nursing homes participated in semistructured focus group interviews. Their WMSDs were not limited to the lower back but involved several body parts. The risk factors for WMSDs included physical, psychosocial, organizational, and personal factors as well as coworkers and clients. However, it is the synergistic effects of long work hours without sufficient rest, work even with musculoskeletal pain because of staff shortages, ineffective management with insufficient prework training and inadequate equipment maintenance, and an aging workforce with strong commitment to resident care that play a crucial role in WMSDs among NAs working in nursing homes. The study found that multidimensional intervention strategies using engineering, administrative, and personal controls should be developed to reduce WMSDs among NAs working in nursing homes.